UJI MIKROBIOLOGIS PAKAN KOMPLIT DARI DAUN TEBU : KAJIAN PERLAKUAN DAN LAMA PEMERAMAN YANG BERBEDA - Liu, Novitasari Maramba; Handayani, Sri; Sumarno, Sumarno (Universitas Tribhuwana Tunggadewi, 2019)
The purpose of this study was to determine the number of lactic acid bacteria and the total number of plates in a complete treatment study of sugarcane leaves and maturation time. This study used a factorial completely randomized design with 6 treatments and 3 replications consisting of factor I: complete feed with sugar cane basal leaves. PI: complete feed with sugar cane leaf base. P2: complete feed with sugar cane leaves plus EM-4. Factor II: long maturation. T0= 0 days of maturation, T5= 5 days of maturation, T10= 10 days maturation, so that 6 treatment were obtained, namely: P1T0= feed complete with basal cane leavers baked for 0 days. P1T5 = complete feed with basic ingredients of sugar cane which is harvested for 5 day. P1T10= complete feed with basal cane leaves harvested for 10 days. P2T0 = compete feed with basic ingredients plus EM-4 baked for 0 days. P2T5= complete feed with sugar cane leaves plus EM-4 added for 5 days, P2T10= complete feed with basic ingredients of sugar cane leaves plus EM-4 which is maintained for 10 days. The results of this study were the number of lactic acid bacteria which included P1T0= 7,1, P1T5= 9,4, P1T10= 11,5, and P2T0= 7,2, P2T5 = 9,6, P2T10= 11,6. The amount of total plate count which includes P1T0= 7,2, P1T5= 9,5, P1T10= 11,5, and P2T0= 7,3, P2T5 = 9,7, P2T10= 11,7. pH value P1T0=6,7,P1T5=4,8, P1T10=4,8 and P2T0=6,4, P2T5=4,7, P2T10=4,6, and crude protein values P1T0=11,51, P1T5=9,01, P1T10=8,7 and P2T0=11,54, P2T5=10,33, P2T10=11,06. Tujuan dari penelitian ini adalah untuk mengetahui jumlah Bakteri Asam Laktat dan Total Plate Count pada pakan komplit daun tebu kajian perlakuan dan lama pemeraman yang berbeda. Penelitian ini menggunakan rancangan acak lengkap pola factorial dengan 6 perlakuan dan 3 ulangan yang terdiri dari: Faktor I :pakan komplit dengan bahan basal daun tebu. P1: pakan komplit dengan bahan basal daun tebu. P2: pakan komplit dengan bahan basal daun tebu ditambah EM-4. Faktor II:Lama pemeraman. T0=Lama pemeraman 0 hari, T5= Lama pemeraman 5 hari, T10= Lama pemeraman 10 hari, sehingga didapat 6 perlakuan yaitu: P1T0=pakan komplit dengan bahan basal daun tebu yang diperam selama 0 hari, P1T5 pakan komplit dengan bahan basal daun tebu yang diperam selama 5 hari, P1T10 pakan komplit daun tebu yang diperam selama 10 hari. P2T0=pakan komplit dengan bahan basal daun tebu ditambah EM-4 yang diperam selama 0 hari, P2T5= pakan komplit dengan bahan basal daun tebu yang diperam selam 5 hari, P2T10= pakan komplit dengan bahan basal daun tebu ditambah EM-4 yang diperam seama 10 hari. Hasil penelitian ini adalah jumlah Bakteri Asam Laktat yang meliputi P1T0=7,1, P1T5=9,4, P1T10=11,5 dan P2T0=7,2, P2T5=9,6, P2T10=11,6. Jumlah Total Plate Count yang meliputi P1T0=7,2, P1T5=9,5, P1T10=11,6 dan P2T0=7,3, P2T5=9,7, P2T10=11,7. Nilai pH P1T0=6,7,P1T5=4,8, P1T10=4,8 dan P2T0=6,4, P2T5=4,7, P2T10=4,6 dan nilai Protein Kasar P1T0=11,51, P1T5=9,01, P1T10=8,7 dan P2T0=11,54, P2T5=10,33, P2T10=11,06.